ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 97/PUU-XIV/2016 TERKAIT KONSTITUSIONALITAS HAK PENGHAYATKEPERCAYAAN DI NEGARA KESATUAN REPUBLIK INDONESIA - Masco Afrianto Lumban Tobing; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
A country cannot be regarded as a state of law if the country concerneddoes not give an award and guarantees protection against human rightsproblems. The idea of human rights is built on the principle of equality. Speakingof the characteristics of the Unitary State of the Republic of Indonesia, thatIndonesia is plurality because it consists of various tribes, languages and customsthat spread from Sabang to Merauke. Likewise, there are various religions andbeliefs that are believed by every citizen. Normatively, regarding the legitimacy ofreligions recognized and regulated in laws and regulations, then Law Number 01/ PNPS / Year 1965 concerning Prevention of Abuse and / or Blasphemy ofReligion constitutes the constitutionality of the type of religious dogmaticsrecognized in the Unitary State of the Republic of Indonesia. After the issuance ofthe Constitutional Court Decision Number 97 / PUU-XIV / 2016 which won therequest of the trustees caused a controversy. Where the verdict raises the reasonfor the government to provide legitimacy also for the existence of belief groups inthe NKRI. However, common sense in the community strongly rejects the equalityof rights for the majority of the followers of the religion with the believers.This type of research can be classified as a type of normative legalresearch, this research is descriptive, namely a study that describes clearly and indetail the constitutionality of belief rights in the Unitary State of the Republic ofIndonesia after the verdict of the Constitutional Court Number 97 / PUU-XIV /2016 read out, data sources Secondary data used consisting of primary legalmaterials, secondary materials, and tertiary legal materials, data collectiontechniques in this study with the library study method, after the data collected isthen analyzed to draw conclusions.From the results of the research problem three main things that can beconcluded. First, the problem of fulfilling the Human Rights of the Believers in theUnitary State of the Republic of Indonesia. second, the existence of Believers inIndonesia after the Constitutional Court Decision concerning Trustees. Third, andthe researcher gave an ideal concept related to the fulfillment of the constitutionalrights of the believers in the Unitary State of the Republic of IndonesiaKeywords: Constitutionali – Human Rights – Inmates of Trust